A Kidnapped Santa Claus - Baum, L. Frank (Lyman Frank), 1856-1919 (Salt Lake City, UT : Project Gutenberg, 1996)
"A Kidnapped Santa Claus" by L. Frank Baum is a Christmas-themed short story published in 1904. Set in the same mythological world as Baum's earlier novel about Santa Claus, the tale features five Daemons who resent Santa's influence over children. When they fail to tempt him into selfishness, envy, and hatred, they kidnap him on Christmas Eve. Santa's magical helpers must scramble to deliver gifts while an army prepares to rescue him$1 (Bbut the resolution brings an unexpected turn involving repentance and forgiveness. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Kidnapped_Santa_Claus
Release date is 1996-05-01
Produced by Dennis Amundson
Keywords: Fantasy literature; Christmas stories; Santa Claus -- Juvenile fiction